Influence of Artocarpus hirsutus (AH) cellulose micro fiber, bamboo fiber in thermoplastic biocomposites - Sumesh Keerthiveettil Ramakrishnan; Kavimani Vijayananth; Ajithram Arivendan; Muhammad Imam Ammarullah (Scientific Reports)
Abstract In this experiment Artocarpus hirsutus (AH) fiber was utilized as the filler material for bamboo fiber (NF)/polyethylene (PE) biocomposites. This was a waste to wealth approach by utilising biomaterial and also can reduce the use of PE plastics. The crystallinity index (Crl) of 45.1%, 56.4%, 67% was observed in AH, alkali treated (NaOH) and cellulose AH fiber respectively. The combination with 20 wt% NF/3 wt% cellulose AH filler observed better tensile and flexural strength. Agglomeration at 4, 5 wt% affects the flexural properties by lesser interfacial adhesion with filler/matrix phase, having properties reducing up to 20.3 MPa. Comparing to cellulose AH filler, both alkali treated and untreated AH filler combinations possess lesser flexural strength. The addition of natural fibers increases the tensile and flexural modulus property with better properties at 30 wt% NF/5 wt% cellulose AH filler combination. The Impact strength doesn’t observe high influence with filler incorporation. This AH fiber hasn’t been explored in detail for mechanical and hydrophilic properties with incorporation with PE matrix. This fabricated composite is suited for bioengineering applications.